Modulation of Stress versus Time Product during Mechanical Ventilation Influences Inflammation as Well as Alveolar Epithelial and Endothelial Response in Rats. (January 2015) - Spieth, Peter M.; Silva, Pedro L.; Garcia, Cristiane S. N. B.; Ornellas, Debora S.; Samary, Cynthia S.; Moraes, Lillian; Bentes, Maira; Morales, Marcelo M.; Kasper, Michael; Güldner, Andreas; Huhle, Robert; Koch, Thea; et al.
Abstract : Background: Mechanical ventilation can lead to lung biotrauma when mechanical stress exceeds safety thresholds. The authors investigated whether the duration of mechanical stress, that is, the impact of a stress versus time product (STP), influences biotrauma. The authors hypothesized that higher STP levels are associated with increased inflammation and with alveolar epithelial and endothelial cell injury. Methods: In 46 rats, Escherichia coli lipopolysaccharide (acute lung inflammation) or saline (control) was administered intratracheally. Both groups were protectively ventilated with inspiratory-to-expiratory ratios 1:2, 1:1, or 2:1 (n = 12 each), corresponding to low, middle, and high STP levels (STPlow, STPmid, and STPhigh, respectively). The remaining 10 animals were not mechanically ventilated. Results: In animals with mild acute lung inflammation, but not in controls: (1) messenger RNA expression of interleukin-6 was higher in STPhigh (28.1 ± 13.6; mean ± SD) and STPlow (28.9 ± 16.0) versus STPmid (7.4 ± 7.5) ( P < 0.05); (2) expression of the receptor for advanced glycation end-products was increased in STPhigh (3.6 ± 1.6) versus STPlow (2.3 ± 1.1) ( P < 0.05); (3) alveolar edema was decreased in STPmid (0 [0 to 0]; median, Q1 to Q3) compared with STPhigh (0.8 [0.6 to 1]) ( P < 0.05); and (4) expressions of vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 were higher in STPlow (3.0 ± 1.8) versus STPhigh (1.2 ± 0.5) and STPmid (1.4 ± 0.7) ( P < 0.05), respectively. Conclusions: In the mild acute lung inflammation model used herein, mechanical ventilation with inspiratory-to-expiratory of 1:1 (STPmid ) minimized lung damage, whereas STPhigh increased the gene expression of biological markers associated with inflammation and alveolar epithelial cell injury and STPlow increased markers of endothelial cell damage. Abstract : In a mild acute lung inflammation model in rats, using mechanical ventilation with an inspiratory-to-expiratory ratio of 1:1 minimized lung damage, whereas an inspiratory-to-expiratory ratio of 2:1 led to increased gene expression of inflammatory mediators and markers of alveolar epithelial cell injury.Supplemental Digital Content is available in the text.